Synergy effects of multi-walled carbon nanotube and graphene nanoplate filled epoxy adhesive on the shear properties of unidirectional composite bonded joints. (February 2020) - Rao, Qiong; Huang, Haixin; Ouyang, Zeyu; Peng, Xiongqi
Abstract: In this paper, multi-walled carbon nanotubes (MWCNTs) and graphene nanoplates (GNPs) were dispersed into epoxy adhesive by sonication method to investigate their synergy effects on the shear properties of unidirectional composite bonded single lap joints (SLJs). The effect of the viscosity of epoxy resin and hardener on the dispersion process was studied. Testing results showed that the incorporation of MWCNTs and GNPs significantly improved the shear strength and elongation of SLJs at failure. 0.75 wt% MWCNTs/GNPs hybrids reached the highest enhancement of shear strength and elongation by 36.6% and 33.2%, respectively. In addition, the thermal stability of epoxy adhesive was improved by nanofillers in some extent. Finally, the failure mode of SLJs and fracture surfaces of the bonding area as well as the damage mechanism of nanofillers were analyzed. Highlights: MCNTs, GNPs and MCNTs/GNPs hybrids were respectively dispersed into epoxy adhesive to improve the shear properties of CFRP joints. The effect of nanofillers on the thermal stability of epoxy adhesive was investigated by TGA analysis. The failure mode of SLJs and fracture surfaces of the bonding area as well as the damage mechanism of nanofillers were studied. The synergy effect of MCNTs/GNPs hybrids were analyzed by SEM images.